Gender Differences in Mathematics Teaching Anxiety Among Pre-Service Mathematics Education Department Students - Alicia Salsabila Putri; Yeshi Nurmala Ari Anti; Wahyunengsih (Tadris Matematika, 2025)
This study aims to determine the differences in anxiety and mathematics commonly experienced by prospective mathematics teachers. This study involved 25 respondents from the Mathematics Education Study Program. This study used a quantitative descriptive analysis approach and collected data in March 2025 using a digital questionnaire with a Likert scale. Descriptive statistics, including percentages, were used to analyze the data. Based on the study findings, female teachers were more anxious than their male counterparts, especially in terms of emotional pressure, teaching readiness, and understanding of gender roles in the classroom. These results indicate that both groups exhibit high levels of self-confidence, despite differences in anxiety levels based on gender. Therefore, to optimally prepare prospective mathematics teachers, teacher education programs should include techniques for managing anxiety in teaching. The small sample size and limited number of respondents are the main limitations of this study.